DEVELOPING SUSTAINABLE QUALITY OF EDUCATION IN INDONESIA USING THE BALANCED SCORECARD: A STUDY OF THE FUNCTIONS AND DUTIES OF THE SCHOOL COMMITTEE - Elvrida N. Sinaga (Scientia Integritas Utama, 2023)
The quality of education in Indonesia internationally is not satisfactory, considering that the quality of education is only ranked 64th out of 120 countries (based on the 2012 UNESCO Education For All Global Monitoring Report), the Education Development Index is only ranked 57th out of 115 countries in 2015 , and its Human Development Index ranks only 110th out of 187 countries. This greatly disrupts the 2030 sustainable education target, in fact the state has regulated the functions and duties of school committees in each school in Indonesia. Based on the literature review, this study produced two conclusions. First, the school committee's business processes as stipulated in the Minister of Education and Culture Regulation Number 75 of 2016 cannot run optimally because they have not focused on strategic communication and performance management. Second, school committees should implement the balanced scorecard (BSC) in improving the quality of education through the report per semester of the headmaster continuously and transparently.